KREASI VAS TERAKOTA PENDUKUNG ARTISTIK OBJEK WISATA PERKEMAHAN BEDENGAN PROGRAM DESA MITRA SELOREJO MALANG - ponimin, Ponimin; Rani, Muhammad Faizal Bin Abdul; Wardana, Mitra Istiar; Vega, Brenda Lydia Ade; Nusantari, Okta Viviana Asmi (Jurnal Abdi Insani, 2025)
The village of Selorejo in the Dau District of Malang Regency has pioneered as a tourism village. The initiative began by developing tourist attractions that made use of forest land along the banks of the Metro River, which was designated as a camping area. However, the development required creative ideas to strengthen the image of the area. Creative elements that can be offered involve creating aesthetic exterior elements of terracotta vases developed by academics, one of whom is from UM, collaborating with competent practitioners in the fields of crafts and landscape architecture. In realizing the creative artistic method, several stages are required, including: (1) design planning or conceptualization with Selorejo Village partners (exploring forms through sketches), (2) followed by the shaping and ornamentation of the terracotta vases, (3) drying and firing the artworks, and (4) displaying the creative terracotta vases at the Bedengan Selorejo Dau Malang Camping Ground (BUPER). The final product is a terracotta vase with a cylindrical base structure that not only offers aesthetic forms but also functional impacts. The upper part of the artwork features a jar-like shape with figurative relief and engraved patterns on all four sides of its surface.